Colitogenic Th1 cells are present in the antigen-experienced T cell pool in normal mice: control by CD4+ regulatory T cells and IL-10. - Asseman, C; Read, S; Powrie, F (2003)
CD4(+) regulatory T cells have been shown to prevent intestinal inflammation; however, it is not known whether they act to prevent the priming of colitogenic T cells or actively control these cells as part of the memory T cell pool. In this study, we describe the presence of colitogenic Th1 cells within the CD4(+)CD45RB(low) population. These pathogenic cells enrich within the CD25(-) subset and are not recent thymic emigrants. CD4(+)CD45RB(low) cells from germfree mice were significantly reduced in their ability to transfer colitis to immune deficient recipients, suggesting the presence of commensal bacteria in the donor mice drives colitogenic T cells into the Ag-experienced/memory T cell pool. This potentially pathogenic population of Ag-experienced T cells is subject to T cell-mediated regulation in vivo by both CD4(+)CD25(+) and CD4(+)CD25(-) cells in an IL-10-dependent manner. Furthermore, administration of an anti-IL-10R mAb to unmanipulated adult mice was sufficient to induce the development of colitis. Taken together, these data indicate that colitogenic Th1 cells enter into the Ag-experienced pool in normal mice, but that their function is controlled by regulatory T cells and IL-10. Interestingly, IL-10 was not absolutely required for CD4(+)CD25(+) T cell-mediated inhibition of colitis induced by transfer of naive CD4(+)CD45RB(high) cells, suggesting a differential requirement for IL-10 in the regulation of naive and Ag-experienced T cells.